Introducing Molecular Functionalities within High Surface Area Nanostructured ITO Electrodes through Diazonium Electrografting. Issue 13 (22nd May 2018) - Kim, Yee‐Seul; Fournier, Sophie; Lau‐Truong, Stéphanie; Decorse, Philippe; Devillers, Charles H.; Lucas, Dominique; Harris, Kenneth D.; Limoges, Benoît; Balland, Véronique
Abstract: Efficient and homogeneous functionalization of 3D nanostructured transparent ITO electrodes was reproducibly achieved by electrochemical reduction of in‐situ generated free‐base porphyrin diazonium salts. The resulting modified electrodes were characterized by cyclic voltammetry and voltabsorptometry, UV‐visible absorption, resonance Raman and XPS. The overall results strongly support the formation of covalently linked electroactive porphyrin oligomers on the ITO surface, that are highly stable towards desorption or hydrolysis in organic as well as mild hydrolytic conditions. Further metalation by zinc ions was quantitatively achieved, thus opening new opportunities for the preparation of robust high‐surface area photoelectrodes with adjustable properties. Abstract : Immobilizing molecular properties : Efficient, homogeneous and stable functionalization of 3D nanostructured transparent ITO electrodes is reproducibly achieved by electrochemical reduction of in‐situ generated free‐base porphyrin diazonium salts.